Observation of a resonant structure near the D+sD−s threshold in the B+→D+sD−sK+ decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Li, Peilian; et al. (Physical review letters, 2023)
An amplitude analysis of the B+→D+sD−sK+ decay is carried out to study for the first time its intermediate resonant contributions, using proton-proton collision data collected with the LHCb detector at center-of-mass energies of 7, 8, and 13 TeV. A near-threshold peaking structure, referred to as X(3960), is observed in the D+sD−s invariant-mass spectrum with significance greater than 12 standard deviations. The mass, width, and the quantum numbers of the structure are measured to be 3956±5±10 MeV, 43±13±8 MeV, and JPC=0, respectively, where the first uncertainties are statistical and the second systematic. The properties of the new structure are consistent with recent theoretical predictions for a state composed of c¯cs¯s quarks. Evidence for an additional structure is found around 4140 MeV in the D+sD−s invariant mass, which might be caused either by a new resonance with the 0++ assignment or by a J/ψϕ↔D+sD−s coupled-channel effect.
*(LHCb Collaboration): R. Aaij, F. Archilli, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und 1048 Personen]
Im Titel sind die Zeichen + und - hochgestellt sowie der Buchstabe s tiefgestellt
Gesehen am 13.02.2024